Earth-abundant Fe1−xS@S-doped graphene oxide nano–micro composites as high-performance cathode catalysts for green solar energy utilization: fast interfacial electron exchange. Issue 8 (23rd January 2018) - Li, Yueqiang; Yin, Jie; Chu, Chaofan; Sui, Ning; Shi, Shaozhen; Wei, Jiazhen; Di, Fangfang; Guo, Junxue; Wang, Can; Xu, Wenli; Zhang, Kaixuan; Li, Xuefeng; et al.
Abstract : DSCs based on Fe1− x S@S-GO–NMC cathode achieved a high solar-to-electrical conversion efficiency up to 7.23%. Abstract : In the process of conversion of solar energy into electricity and fuel, efficient electrocatalysts are indispensable. Rieske iron–sulfur protein and FeS catalysts play an important role in natural photosynthesis (NPS), and in artificial photoelectrochemical cells, respectively. Nano–micro composite catalysts (NMCCs) possess not only high catalytic activity but also fast electron transport. Herein, we prepared a nano–micro composite (NMC) of Fe1− x S nanoparticles decorated on sulfur-doped graphene oxide (S-GO) sheets (namely, Fe1− x S@S-GO–NMC) to be used as a cathode in dye-sensitized solar cells (DSCs). The GO effectively inhibit the aggregation of Fe1− x S nanoparticles. Notably, DSCs based on an Fe1− x S@S-GO–NMC cathode achieved a high solar-to-electrical conversion efficiency up to 7.23%. The conversion efficiency is, to our knowledge, one of the highest efficiencies for DSCs based on an FeS or FeS2 cathode. Although the Fe1− x S@S-GO–NMC exhibited a low thermodynamic possibility for redox reactions, it showed a higher kinetic rate than that of Pt for the charge transfer between the reaction medium and the cathode. This indicates that a fast electron exchange process occurs at the interface between the reaction and the cathode. The value of the time constant ( τ ) corresponding to the charge exchange resistance based on Fe1− x S@S-GO–NMC (0.0215 ms) was smaller than that obtained with Pt (0.261 ms). Therefore, we ascribed the superior performance of the photoelectrochemical device based on Fe1− x S@S-GO–NMC to its good electrocatalytic performance. The results are of great interest for fundamental research and for practical applications of FeS and FeS2 and their composites in the solar splitting of water, artificial photoelectrochemical cells, and electrocatalysts.